The Design of Information System of Service Order Implementation Monitoring at Information Technology (IT) Maintenance Division - Dewi Kania Widyawati (Politeknik Negeri Lampung, 2012)
The information system of service order implementation monitoring of IT maintenance at an organization or company has an important role to support its work and business. Considering the important role of IT at companies, all the IT equipments must be in good condition and be ready to use. Service order implementation monitoring can help the Head of IT Maintenance Division monitor the progress of his/her division work so that the division work performance will improve. The methods of system development are analysis and structure design methods. The approaches of system development are structured approach, top-down approach, and modular approach. This system design can also minimize usersâ€™ work obstacles due to uncontrolled completion time of IT service order.Â Keywords: service order, information technology, structured approach, top-down approach, and modular approach.